Afro-Feminism and Racism in Toni Morrison’s The Bluest Eye - Shikha Jain; Dr. Namita Chouhan (International Journal of Scientific Research in Humanities and Social Sciences, 2024)
Toni Morrison’s The Bluest Eye is a seminal work that explores the intersections of racism, sexism, and colourism within the lived experiences of Black women and girls. This paper examines the novel through an Afro-feminist lens, highlighting how Morrison critiques the internalization of white beauty standards and the compounded oppression faced by Black women. By analyzing the characters of Pecola Breedlove, Claudia MacTeer, and other key figures, this paper discusses the ways in which racism and patriarchy shape Black female identity and self-worth. Morrison’s narrative ultimately serves as a powerful critique of the structures that dehumanize and marginalize Black women.